2005
DOI: 10.1029/2004jd005670
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations of the Na and Fe layers at the South Pole and their implications for the chemistry and general circulation of the polar mesosphere

Abstract: [1] Lidar observations, conducted at the South Pole by University of Illinois researchers, are used to characterize the seasonal variations of mesospheric Na and Fe above the site. The annual mean layer abundances are virtually identical to midlatitude values, and the mean centroid height is just 100 m higher for Na and 450 m higher for Fe compared with 40°N. The most striking feature of the metal profiles is the almost complete absence of Na and Fe below 90 km during midsummer. This leads to summertime layers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
130
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(149 citation statements)
references
References 59 publications
17
130
0
Order By: Relevance
“…This loss of atomic Na is expected from the temperaturedependence of the mesospheric Na chemistry as discussed by Plane et al [1999]. Note that the summertime minimum is even more pronounced near 60°N, most likely because of the uptake of Na species onto ice particles above 80 km [Gardner et al, 2005].…”
Section: Global Results and Validationmentioning
confidence: 99%
“…This loss of atomic Na is expected from the temperaturedependence of the mesospheric Na chemistry as discussed by Plane et al [1999]. Note that the summertime minimum is even more pronounced near 60°N, most likely because of the uptake of Na species onto ice particles above 80 km [Gardner et al, 2005].…”
Section: Global Results and Validationmentioning
confidence: 99%
“…In fact, previous observations have shown that the associated correlation coefficients among temperature, Fe and Na densities are often quite high (absolute values greater than 0.7) but the sign can vary rapidly near the peaks of the Na and Fe layers [Gardner and Liu, 2010;Gardner et al, 2005;Chen and Yi, 2011]. For chemically active constituents such as Fe and Na, the fluctuations arise from purely dynamical effects associated with wave-induced displacement, as well as chemical effects associated with the perturbed production and loss reactions involving the species.…”
Section: Lidar Observationsmentioning
confidence: 99%
“…The ratios between these two channels are used to derive the Fe temperature in the MLT region by employing the Boltzmann technique [Gelbwachs, 1994;Chu et al, 2002]. Over the last decade, this lidar has been deployed to the Pacific Ocean, the North Pole, the South Pole, and Rothera, Antarctica, under harsh environment [Chu et al, 2000;Gardner et al, 2001Gardner et al, , 2005Gardner et al, , 2011], so we must refurbish and upgrade the lidar to restore and enhance its capabilities before deploying it to McMurdo, Antarctica, in November 2010 [Chu et al, 2011a]. Such refurbishment and upgrade along with extensive sky tests were conducted at the University of Colorado [Z. , which led to the Boulder observations in 2010.…”
Section: Boulder Campaign 2010mentioning
confidence: 99%
See 2 more Smart Citations